ON THE QUESTIONNAIRE ON THE CONCEPTUAL APPARATUS OF FINANCIAL STABILITY OF THE BANKING SYSTEM - Погореленко, Наталія (Socio-economic relations in the digital society, 2019)
The article is devoted to the defi nition of meaningful characteristics of the notion «financial stability ofthe banking system», which allows to isolate and systematize the most important ones, distinguish them from other related concepts, and further use it in the process of developing tools for ensuring the financial stability of the banking system. For the allocation of content components and clarifi cation of the concept of «fi nancial stability of the banking system», content analysis was used, which is a formalized method of analysis of textual and graphical information, the main and central tool of which is the system of categories.Based on the study of the content of the category «financial stability of the banking system», the systematization and ranking of its key components were carried out through the content analysis procedure — in terms of the theoretical approach and approach of the central banks of diff erent countries. The common components are singled out, which are included in the structure of the own interpretation of theinvestigated concept. Th e importance of introducing into the defi nition of «fi nancial stability of the banking system» the criterion of effi ciency is emphasized and its connection with financial stability is defi ned, which implies not only constant, but also eff ective ability to perform the assigned functions. The importance of introducing into the composition of the investigated category of risk component is proved, which in the current conditions of banking activity is not suffi ciently specified theoretically, but is practically included in the composition of the relevant macroprudential procedures.
Keywords: banking system; financial stability; content analysis; components; ranking; efficiency; risks